(untitled) (Research, Society and Development, 2024)
Applied behavior analysis emphasizes the importance of performing a functional assessment before developing a treatment for the problem behavior. Beavers et al. and Hanley et al. establish Functional Analysis as the gold standard functional assessment procedure in treating severe problem behaviors. However, there is little information on how practitioners use functional assessment in settings applied to individuals with developmental or no delay. The present study aimed to replicate the Roscoe et al. study and research in which various types of functional assessment are implemented in institutions that serve individuals with atypical development in Brazil. In total, 103 participants answered the forms. Still, only 25.2% related use most functional analysis than a descriptive and indirect assessment to inform an intervention plan for problem behavior. However, 79.6% relate that functional analysis is necessary to inform treatment for problem behavior. We conclude that there is an evolution since Roscoe et al., at least related to comprehension of what is most necessary. Still, we have not seen much improvement in the application of functional analysis.